A qualitative investigation of specialist orthodontists in New Zealand: Part 2. Orthodontists' working lives and work-life balance - Soma Kieran J.; Murray Thomson W.; Morgaine Kate C.; Harding Winifred J. (Sciendo, 2012)
Background: Orthodontics is the most widely practised form of specialist dentistry in New Zealand. To date, no known qualitative research has been published examining the work-life balance of practitioners. The aim of this study was to investigate the working lives and work-life balance of NZ orthodontists in order to generate an understanding of the reality of orthodontic specialist practice and its effects on orthodontists' professional and personal lives.